Effect of Ampicillin on the kinetics of colonization of Streptococcus pneumoniae and Lactobacillus fermentum in the respiratory tract of mice - Silva Clara; Cecilia Marta; Santos Viviana; Cangemi de Gutiérrez Rosa; Nader-Macías María (BMC, 2004)
Abstract Ampicillin was selected to further study the effect of this antibiotic on the colonization capability of S. pneumoniae and L. fermentum intranasally inoculated in a mice experimental model. The sensitivity of S. pneumoniae and L. fermentum to antibiotics was evaluated by different "in vitro" techniques. The results showed that both microorganisms have a typical pattern of sensitivity to antibiotics in these assays. The "in vivo" experiments showed that the treatment with Ampicillin increased the number of lactobacilli and neumococci in the groups of mice treated only with one of the microorganisms. In those mice treated with Lactobacillus, challenged later with neumococci and treated with Ampicillin, the pathogen in lung decreased on the 4th day, disappearing completely after on. The histological studies showed that the antibiotic treatment decreased the inflammatory response produced by the pathogen at the lung and trachea levels.